Phase II, 2‐stage, 2‐arm, PIK3CA mutation stratified trial of MK‐2206 in recurrent endometrial cancer. Issue 2 (13th December 2019) - Myers, Andrea P.; Konstantinopoulos, Panagiotis A.; Barry, William T.; Luo, Weixiu; Broaddus, Russell R.; Makker, Vicky; Drapkin, Ronny; Liu, Joyce; Doyle, Austin; Horowitz, Neil S.; Meric‐Bernstam, Funda; Birrer, Michael; et al.
Abstract : Endometrial cancers have high rates of phosphoinositide 3‐kinase (PI3K) pathway alterations. MK‐2206 is an allosteric inhibitor of AKT, an effector kinase of PI3K signals. We hypothesized patients with tumors harboring PIK3CA mutations would be more likely to benefit from MK‐2206 than those without PIK3CA mutation. A Phase II study was performed in patients with recurrent endometrial cancer; all histologies except carcinosarcoma were eligible. Up to two prior chemotherapy lines were permitted, excluding prior treatment with PI3K pathway inhibitors. The first 18 patients were treated with MK‐2206 200 mg weekly. Due to unacceptable toxicity, dose was reduced to 135 mg. Co‐primary endpoints were objective response rate (ORR) and progression‐free survival at 6 months (6moPFS). Thirty‐seven patients were enrolled (one ineligible). By somatic PIK3CA mutation analysis, nine patients were mutant (MT) [one with partial response (PR)/6moPFS, two with 6moPFS]. Twenty‐seven patients were wild‐type (WT) (one PR and four 6moPFS). Most common toxicities were rash (44%), fatigue (41%), nausea (42%) and hyperglycemia (31%). Grade 3 and 4 toxicities occurred in 25 and 17% of patients, respectively. Exploratory analysis found serous histology had greater 6moPFS as compared to all other histologies (5/8 vs . 2/28, p = 0.003). PTEN expression was associated with median time to progression ( p = 0.04). No other significant associations with PI3K pathway alterations were identified. There is limited single agent activity of MK‐2206 in PIK3CA MT and PIK3CA WT endometrial cancer populations. Activity was detected in patients with serous histology and due to their poor outcomes warrants further study (NCT01307631). Abstract : What's new? Endometrial cancers have the highest reported rate of PI3K pathway alterations of any solid tumor. A kinase inhibitor called MK‐2206, which blocks the PI3K pathway, has entered Phase II clinical trials. In this study, the authors predicted that tumors with PIK3CA mutations would be more susceptible to MK‐2206 than those without. However, this was not the case, and toxicity was also higher than expected. One group of patients did show clinical benefit: those whose tumors had serous histology. MK‐2206 is thus being further explored in these patients.